Pengaruh Return On Asset, Return On Equity, dan Net Profit Margin Terhadap Pertumbuhan Laba Pada Industri Perbankan - Alfiani, Ria; Hutagaol, Layon Hocben (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025), 2025)
This research aims to determine the effect of Return On Assets, Return On Equity and Net Profit Margin on profit growth in the banking industry. This research uses quantitative descriptive methods. The research population consists of companies in the banking industry listed on the Indonesia Stock Exchange in 2018–2022. The sampling method applied in this research was purposive sampling. The number of samples in this research was 26 companies in the banking industry. The data analysis technique used is multiple linear regression analysis using SPSS 25. Based on the research results, it shows that Return On Assets partially has a negative and significant effect on profit growth. Return On Equity and Net Profit Margin partially have a positive and significant effect on profit growth, simultaneously Return On Assets, Return On Equity and Net Profit Margin effect banking industry profit growth.   Keywords : Return On Asset, Return On Equity, Net Profit Margin, Profit Growth